PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN INSENTIF TERHADAP SEMANGAT KERJA KARYAWAN DI PT FEDERAL INTERNATIONAL FINANCE (FIF GROUP) CABANG SERANG (Faletehan Jurnal Ekonomi dan Bisnis, 2023)
Andini Agustina Evandri, NPM : 18010130, Research Title "The Influence of TransformationalLeadership and Incentives on Employee Morale at PT Federal International Finance (FIFGroup) Serang Branch" under the guidance of Mr. Heri Sapari Kahpi, SE,. MM as Advisor 1and Mother Sucihati, SE,. MM as Advisor 2.This study was conducted to determine the effect of transformational leadership on employeemorale, to determine the effect of incentives on employee morale and to determine the effect oftransformational leadership and incentives on employee morale at PT FIF Group SerangBranch.This type of research is quantitative, with data collection techniques through primary dataincluding questionnaires for employees of PT FIF Group Serang Branch. The population in thisstudy were 58 employees, while the sampling technique was saturated sampling, which took allmembers of the population so that the sample used in this study was 58 employees of PT FIFGroup Serang Branch. The data analysis technique used multiple regression with the SPSS 21program.The results obtained in Hypothesis 1 that there is an influence of transformational leadershipon employee morale at PT FIF Group Serang Branch with the results tcount > ttable (2,965 >2.003) with a significance level of 0.00 (0.00 < 0.05). Hypothesis 2 obtained that there is aneffect of incentives on employee morale at PT FIF Group Serang Branch with the results tcount> ttable (5.501 > 2.003) with a significance level of 0.00 (0.00 < 0.05). Hypothesis 3 there isan influence between transformational leadership and incentives on employee morale at PTFIF Group Serang Branch with the results Fcount > Ftable (19,926> 3,165) with asignificance level of 0.00 (0.00 < 0.05)